Exploring the Novel Alternative and Modern Treatment Options for Polycystic Ovary Syndrome-A Review - Stephanie Mohammed; Brian N. Cockburn; Venkatesan Sundaram (Integrative Medicine Reports)
Introduction: Polycystic ovary syndrome (PCOS) is a widespread endocrine disorder that affects millions of women globally. The conventional approach to managing PCOS involves dietary adjustments, lifestyle modifications, pharmacological interventions, and in some cases, surgical procedures. This comprehensive review is dedicated to exploring novel treatment options for PCOS, with a specific focus on physical modalities, herbal approaches, holistic therapies, medical procedures, bacteriotherapeutics, and supplements. Method: To conduct this review, a systematic literature search was carried out up to 2023, utilizing reputable databases such as PubMed, Embase, Google Scholar, and the Cochrane Library. The search identified 33 key articles meeting the inclusion criteria, which encompassed both animal and human studies concentrating on PCOS and innovative interventions. The primary emphasis during the evaluation was on efficacy and safety. The articles were organized into six distinct groups: holistic therapies, herbal and natural approaches, physical modalities, medical procedures, bacteriotherapeutics, and supplements. Quality assessment involved the use of the Cochrane risk-of-bias tool and Assessment of Multiple Systematic Reviews (AMSTAR) 2. Results: The review unveiled a spectrum of interventions, ranging from acupuncture, yoga, and herbal remedies to high-intensity ultrasound, ultrasound cavitation, probiotics, fecal microbiota transplantation, and supplements. While some interventions exhibited promising results, conflicting reports and uncertainties persisted. Notably, positive effects on insulin resistance and androgen levels were observed with supplements. The intricate nature of PCOS treatments underscores the need for evidence-based strategies. Conclusion: While noninvasive and natural treatments show promise in the management of PCOS, rigorous research is indispensable to evaluate their long-term safety and optimal clinical utilization. The integration of lifestyle changes, conventional therapies and novel treatments, presents a potential avenue for a comprehensive and effective approach to treating PCOS, offering hope to millions of affected women worldwide. Caution is advised in the emerging realm of alternative treatments, and consulting health care professionals for informed decision-making in PCOS management continues to be strongly recommended.